2017
DOI: 10.11613/bm.2018.010701
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of CKD-EPI predictive equation in estimating chronic kidney disease prevalence in the Croatian endemic nephropathy area

Abstract: IntroductionChronic kidney disease (CKD) is a significant public health problem and it is not possible to precisely predict its progression to terminal renal failure. According to current guidelines, CKD stages are classified based on the estimated glomerular filtration rate (eGFR) and albuminuria. Aims of this study were to determine the reliability of predictive equation in estimation of CKD prevalence in Croatian areas with endemic nephropathy (EN), compare the results with non-endemic areas, and to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Forty two laboratories in our study still used the MDRD equation. Fuček et al showed that eGFR based on CKD-EPI equations correlated significantly with endemic nephropathy ( 16 ). Another new option for eGFRcrea is the Lund-Malmö equation ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Forty two laboratories in our study still used the MDRD equation. Fuček et al showed that eGFR based on CKD-EPI equations correlated significantly with endemic nephropathy ( 16 ). Another new option for eGFRcrea is the Lund-Malmö equation ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This data was then processed to generate new candidate predictors based on data collected in the first 6 or 12 months post-transplantation, separately. Specifically, eGFR was calculated using the CKD-EPI equation, which is based on serum creatinine (Scr, μmol/L), gender, and age [ 34 ]. NLR, PLR, and MLR were generated via the divisions of neutrophil count, platelet count, and monocyte count by lymphocyte count, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of metformin dose is recommended when eGFR is 30‐44 mL/min/1.73 m 2 (stage 3b) and discontinuation when eGFR is <30 mL/min/1.73 m 2 (stages 4 and 5). eGFR can be calculated from serum creatinine and/or cystatin C. eGFRcrea is the most common test for estimation of GFR in clinical practice . KDIGO guidelines recommend confirming eGFRcrea decline below 45 mL/min/1.73 m 2 by determination of eGFRcys or direct GFR measurement for metformin dosing .…”
Section: Introductionmentioning
confidence: 99%
“…eGFR can be calculated from serum creatinine and/or cystatin C. eGFRcrea is the most common test for estimation of GFR in clinical practice. 2 KDIGO guidelines recommend confirming eGFRcrea decline below 45 mL/min/1.73 m 2 by determination of eGFRcys or direct GFR measurement for metformin dosing. 3 Real-world practice of monitoring diabetic patients does not include the gold standard of GFR measurement.…”
Section: Introductionmentioning
confidence: 99%